2014
DOI: 10.1039/c4cp01206b
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the Rayleigh light scattering properties of atmospheric pre-nucleation clusters

Abstract: The Rayleigh and hyper Rayleigh scattering properties of the binary (H2SO4)(H2O)n and ternary (H2SO4)(NH3)(H2O)n clusters are investigated using a quantum mechanical response theory approach. The molecular Rayleigh scattering intensities are expressed using the dipole polarizability α and hyperpolarizability β tensors. Using density functional theory, we elucidate the effect of cluster morphology on the scattering properties using a combinatorial sampling approach. We find that the Rayleigh scattering intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 81 publications
8
62
0
Order By: Relevance
“…43,72 The depolarization ratios α ̅ and anisotropic polarizabilities Δα are very much size dependent, which is consistent with the study of sulfuric acid hydration systems. 72 The influence of different numbers of the sulfuric acid molecules on the Rayleigh light scattering can be observed from the different lines with different colors in Figures 8−11. The Rayleigh light scattering intensities R n and isotropic mean polarizabilities α ̅ increase with increasing numbers of sulfuric acid molecules, which is consistent with the influence of the water molecules.…”
Section: ■ Methodssupporting
confidence: 68%
“…43,72 The depolarization ratios α ̅ and anisotropic polarizabilities Δα are very much size dependent, which is consistent with the study of sulfuric acid hydration systems. 72 The influence of different numbers of the sulfuric acid molecules on the Rayleigh light scattering can be observed from the different lines with different colors in Figures 8−11. The Rayleigh light scattering intensities R n and isotropic mean polarizabilities α ̅ increase with increasing numbers of sulfuric acid molecules, which is consistent with the influence of the water molecules.…”
Section: ■ Methodssupporting
confidence: 68%
“…66 The benchmark for the smallest clusters of H 2 SO 4 -NH 3 -H 2 O was determined by Elm et al 84 They found that CAM-B3LYP/aug-cc-pVDZ gave a good balance between efficiency and accuracy and obtained good agreement with both experimental and CCSD(T) values of polarizability. The light scattering intensities and isotropic mean polarizabilities a, as well as anisotropic polarizabilities Da, were calculated at the CAM-B3LYP/ aug-cc-pVDZ level of theory and the relevant computational methods are given in our earlier study.…”
Section: Methodsmentioning
confidence: 99%
“…40 All presented calculated optical properties are given in atomic units (a.u.). These were obtained by adding acid-base pairs to the existing cluster structures and minimizing using an on-the-fly MMFF94 force field using a simulating annealing approach while keeping the cluster as spherical as possible.…”
Section: Computational Methodologymentioning
confidence: 99%
“…Currently, very little is known about the direct atmospheric impact of these clusters and due to the high concentrations the Rayleigh light scattering properties of this background pool of molecular clusters might not be negligible. 40 This approach makes it possible to investigate non-spherical particles. While nucleation is currently believed to occur via the formation of small molecular clusters, very little is known about the exact mechanisms.…”
Section: Introductionmentioning
confidence: 99%